The effectiveness of a specialised oral nutrition supplement on outcomes in patients with chronic wounds: a pragmatic randomised study. Issue 5 (30th April 2013) - Bauer, J. D.; Isenring, E.; Waterhouse, M.
Abstract Background Nutrition supplements enriched with immune function enhancing nutrients have been developed to aid wound‐healing, although evidence regarding their effectiveness is limited and systematic reviews have lead to inconsistent recommendations. The present pragmatic, randomised, prospective open trial evaluated a wound‐specific oral nutrition supplement enriched with arginine, vitamin C and zinc compared to a standard supplement with respect to outcomes in patients with chronic wounds in an acute care setting. Methods Twenty‐four patients [11 males and 13 females; mean (SD) age: 67.8 (22.3) years] with chronic wounds (14 diabetic or venous ulcers; 10 pressure ulcers or chronic surgical wounds) were randomised to receive either a wound‐specific supplement (n = 12) or standard supplement (n = 12) for 4 weeks, with ongoing best wound and nutrition care for an additional 4 weeks. At baseline, and at 4 and 8 weeks, the rate of wound‐healing, nutritional status, protein and energy intake, quality of life and product satisfaction were measured. Linear mixed effects modelling with random intercepts and slopes were fitted to determine whether the wound‐specific nutritional supplement had any effect. Results There was a significant improvement in wound‐healing in patients receiving the standard nutrition supplement compared to a wound‐specific supplement (P = 0.044), although there was no effect on nutritional status, dietary intake, quality of life and patient satisfaction. Conclusions The results of the present study indicate that a standard oral nutrition supplement may be more effective at wound‐healing than a specialised wound supplement in this clinical setting.